Prevalence of Visual Impairment in Preschool Children in Southern China - Wang, Hongxi; Qiu, Kunliang; Yin, Shengjie; Du, Yali; Chen, Binyao; Jiang, Jiao; Deng, Dandan; Zhang, Mingzhi (Frontiers in Public Health, 2022)
Purpose: To assess the prevalence and distribution of visual impairment in preschool children in southern China. Methods: Preschool children aged 36 to 83 months were enrolled in a vision screening program in Shantou City. Visual acuity test and noncycloplegic refraction were conducted. According to the American Academy of Ophthalmology (AAO) guidelines, visual impairment was defined as UCVA in either eye less than 20/50, 20/40 and 20/32 at aged 36 to 47, 48 to 59 and 60 to 83 months, respectively, as well as an interocular difference (IOD) of ≥ two lines of UCVA. Results: The UCVA test was successfully performed in 7880 children (94.6% of the enrolled population). A total of 938 (11.9%; 95% CI, 11.2-12.6) children were found with reduced UCVA in the worse eye, and 393 (5.0%; 95% CI, 4.5-5.5) children had an IOD of two or more lines. Combining the reduced UCVA with IOD criteria identified 1032 (13.1%; 95% CI, 12.4-13.8) children with visual impairment. UCVA in preschool children improved with age naturally and boys had slightly better age-adjusted UCVA than girls. The causes of reduced visual acuity included uncorrected refractive error, amblyopia, congenital cataract and others. The cylindrical diopter in right eye in children with reduced vison was higher than that in children with normal vision (1.19 ± 1.05 vs 0.52 ± 0.49, P < 0.001). A total of 146 (1.9%, 95% CI, 1.6-2.2) preschool children wore spectacles. The proportion of wearing spectacles increased with age (χ2 = 35.714, P < 0.001), but with IOD increasing by 0.1 logMAR, the Odds of wearing spectacles decreased by 44.8%. Conclusions: The current study provided data on the prevalence of visual impairment in preschool children in China upon a large-scale school-based vision screening. Further study should be conducted to verify the benefit from vision screening.